Three and Six Months of Ketogenic Diet for Intractable Childhood Epilepsy: A Systematic Review and Meta-Analysis - Liu, Xian Yu; Chen, Jing; Zhu, Min; Zheng, Guo; Guo, Hu; Lu, XiaoPeng; Wang, Xiaoyu; Yang, Xiao (Frontiers in Neurology, 2019)
Objective: The ketogenic diet (KD) has been an effective antiepileptic treatment for intractable childhood epilepsy. The appropriate timing to evaluate the effect of KD is 3 months which is still not defined statistically. Therefore, we aim to realistically assess whether spasm remission during the period of 3 months KD can be a prediction index for the therapeutic effect of 6 months treatment. Methods: To investigate the duration and effect of the KD therapy for intractable childhood epilepsy, we searched the relevant articles up to May 20, 2018 from PubMed, Cochrane, Embase, Ovid, Web of Science, Google Scholar, and Conference literature. The inclusion criteria were: (i) confirmed cases of intractable childhood epilepsy, (ii) specific 3 and 6 months follow-up time, (iii) classified spasm remission evaluation. The exclusion criteria were: (i) including other therapy, (ii) unspecific follow-up time, (iii) no specific index for seizure reduction. The data extracted by two researchers independently included proportion of KD duration, seizure remission, year of publication, author, study design, and diet varieties. Results: The search strategy included a total of 542 citations, 18 articles were met the criteria with a total of 1,062 patients included in the final analysis. Compared with 3 and 6 months KD treatment, the rate difference of 50% seizure reduction was −0.01(95% CI: −0.09 to 0.06). And 90% seizure reduction was −0.036(95% CI: −0.090 to 0.017) and seizure free was −0.031(95% CI: −0.081 to 0.020). Conclusion: This meta-analysis provides statistical support that a period of 3 months KD can be a prediction index of 6 months duration in term of spasm remission. The 3 months KD can be implemented to evaluate seizure remission timely and provide personalized early support.